Numerical Simulation of the Effects of Grassland Degradation on the Surface Climate in Overgrazing Area of Northwest China - Yanfei Li; Zhaohua Li; Zhihui Li; Xiaoli Geng; Xiangzheng Deng (Advances in Meteorology)
The climatic effects of LUCC have been a focus of current researches on global climate change. The objective of this study is to investigate climatic effects of grassland degradation in Northwest China. Based on the stimulation of the conversion from grassland to other land use types during the next 30 years, the potential effects of grassland degradation on regional climate in the overgrazing area of Northwest China from 2010 to 2040 have been explored with Weather Research and Forecasting model (WRF). The analysis results show that grassland will mainly convert into barren land, croplands, and urban land, which accounts for 42%, 48%, and 10% of the total converted grassland area, respectively. The simulation results indicate that the WRF model is appropriate for the simulation of the impact of grassland degradation on climate change. The grassland degradation during the next 30 years will result in the decrease of latent heat flux, which will further lead to the increase of temperature in summer, with an increment of 0.4–1.2°C, and the decrease of temperature in winter, with a decrement of 0.2°C. In addition, grassland degradation will cause the decrease of precipitation in both summer and winter, with a decrement of 4–20 mm.